The Matter of Methodology of Examination in Physics - Rupšlaukis, Edmundas; Bitinas, Bronislovas (Acta Paedagogica Vilnensia, 1998)
A quantitative and qualitative analysis of the examination results of the secondary school course in physics (1995/96 school year) has been given in the article. The analysis has been carried out using the complex computer programme „PAULA". Most attention has been given to surveying the ways which are used by the learners to accomplish certain tasks which make up the contents of the exam. Conclusions about the quality of school-leaver's preparation have been formulated and the ways of improving the methodology of designing and developing the school – leaving exam in physics have been outlined.
Keywords: secondary school; physics teaching; exam in physics; methodology of examination